Reading prophetic narratives - Simon, Uriel (Indiana studies in biblical literature., 1997)
"Noted biblical scholar Uriel Simon undertakes a systematic study of prophetic narratives in the Bible. He focuses on seven stories, analyzing their form and structure, their rhetorical devices, their descriptions of character and motive, their narrative techniques - in short, on the ways in which the stories are told. Simon begins with the premises that biblical stories were meant for readers, not critics, and that we need to recover the distinctive ways of reading appropriate to biblical storytelling. He provides careful readings of prophetic stories such as Samuel's call to prophecy, Saul at Endor, and David and Bathsheba. Simon's interpretations are always enlightening and will provide contemporary readers with an enriched understanding of these timeless narratives."--Jacket